THE APPLICATION OF TRIDIAGONAL MATRIX ALGORITHM IN CUBIC SPLINE INTERPOLATION - Elvathna Syafwan; EfendI -; Narwen -; Mahdhivan Syafwan (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
Tridiagonal matrix algorithm is known to be more efficient in the computational process than theGaussian elimination method in solving linear system problems involving tridiagonal matrices. Inthis paper, the tridiagonal matrix algorithm is applied to the cubic spline interpolation problem withnatural boundary conditions. In this case, the tridiagonal matrix algorithm plays a role in findingthe second derivative of each cubic spline sub-function so that it is more efficient in obtaining thecoefficients of the third order polynomials that form the cubic spline function